PENGARUH PERSONALIZED LEARNING TERHADAP MOTIVASI DAN KEMANDIRIAN BELAJAR SISWA DI SMAN 1 KOTA JAMBI - Fitriah; Muhammad Arif Liputo; ⁠⁠Romi Kurniadi (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
21st-century education demands learning strategies that are able to adapt to the needs and characteristics of individual students. Personalized learning is one relevant approach because it is designed based on students' interests, abilities, and learning styles. This approach is in line with constructivism theory which emphasizes the active role of students in building knowledge through meaningful learning experiences. Motivation and learning independence are two important aspects that can be improved through the implementation of personalized learning. This study aims to determine the effect of personalized learning on the motivation and learning independence of class XI F4 students at SMAN 1 Jambi City. This study uses a quantitative approach with an experimental method and a Pre-Experimental One Group Pretest-Posttest Design. The research sample was 36 students selected through purposive sampling technique from a population of 143 class XI students. The instruments used were pretest and posttest questionnaires to measure motivation and learning independence. Data were analyzed using descriptive statistics and Paired Sample T-Test. The results showed that personalized learning has a positive and significant effect on students' motivation and learning independence, with a significance value of 0.000 (p < 0.05). However, the N-Gain test results indicated a low level of learning effectiveness, due to the short duration of the intervention and its early implementation. Nevertheless, personalized learning still shows potential for encouraging students to be more motivated and independent. This study recommends the continued implementation of personalized learning with appropriate strategies to optimize overall student learning outcomes.